2017
DOI: 10.1039/c7gc02682j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient synthesis of β-nitrate ester carboxamides through the ring-opening of 2-oxazolines

Abstract: A novel method for the synthesis of β-nitrate ester carboxamides using non-corrosive tert-butyl nitrite (TBN) as the nitro source and easily available oxygen as the oxidant has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Focusing on the biological importance and industrial application of the 2‐oxazolines Guo et al. reported an efficient metal‐free protocol for the synthesis of β‐nitrate ester carboxamides ( 92 ) from 2‐substituted oxazolines ( 91 ) via ring‐opening of the oxazole ring (Scheme ) …”
Section: Outlines Of the Reactions Involving Tbnmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the biological importance and industrial application of the 2‐oxazolines Guo et al. reported an efficient metal‐free protocol for the synthesis of β‐nitrate ester carboxamides ( 92 ) from 2‐substituted oxazolines ( 91 ) via ring‐opening of the oxazole ring (Scheme ) …”
Section: Outlines Of the Reactions Involving Tbnmentioning
confidence: 99%
“…Focusing on the biological importance and industrial application of the 2oxazolines Guo et al reported an efficient metal-free protocol for the synthesis of b-nitrate ester carboxamides (92)f rom 2substituted oxazolines (91)v ia ring-opening of the oxazole ring (Scheme66). [98] Based on the literature precedents at entative mechanism is proposed. Initially,T BN undergoes homolytic cleavaget og ive Scheme63.…”
Section: Nitrationmentioning
confidence: 99%
“…Chemie cyclopropane 8 in 83 %yield, whereas its reduction with LAH followed by N-benzoylation afforded the methylamino derivative 9 in 63 %y ield over two steps.O fn ote,m ethylaminocyclopropanes constitute the core structure of marketed drugs such as Tasimelteon [16] and Levomilnacipran. [17] Finally, az inc-catalyzed [2+ +3] cycloaddition reaction of 3a with NaN 3 [18] gave the tetrazole-substituted cyclopropane 10, whereas ar eaction with aminoethanol and zinc chloride [19] afforded the oxazoline-functionalized cyclopropane 11 in good yields (39-84 %). In most cases,t he transformation of the nitrile group occurred with no erosion of enantiopurity (> 99 % ee,Scheme 3).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Zhang et al. developed a novel method for β‐nitrate ester carboxamides synthesis using the non‐corrosive tert‐butyl nitrite (TBN) as the nitro source and easily available oxygen as the oxidant, providing a facile method to synthesis of nicorandil . In addition, there are many outstanding reports about halogenation reactions .…”
Section: Introductionmentioning
confidence: 99%